Uncertainty analysis of spectral flux measurement using Monte Carlo simulation - Yaran, Senel; Kosemen, Zuhal Alpaslan; Akkan, Cagri Kaan; Nisanci, Hilal Fatmagul; Kruger, Udo; Sperling, Armin (Edp Sciences S A, 2024)
In photometry, spectrally integrated quantities are commonly used, and their uncertainties are calculated using classical approaches. Since determining correlations at different wavelengths and effects on spectrally integrated quantities is rather complex, a noise modification of the spectral value using Monte Carlo simulation was applied to estimate unknown correlations in the uncertainty of total luminous flux based on integrated spectral luminous flux values. For this aim, an LED with 6500 K correlated colour temperature was measured in an integrated sphere flux measurement system. The correlations between the measurements at different wavelengths were analysed, and the uncertainty boundaries of the integrated quantity and total luminous flux were obtained.
Keywords: Uncertainty; Monte Carlo; Base functions; Integrated quantities; Correlations between quantities at different wavelengths